(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The aim of this article is to point out the contributions of phenomenology and existential psychoanalysis to the development of an in-depth analysis of psychic dynamics and their relationship with consciousness. In this sense, we will use a classic case from the literature contained in Studies on Hysteria by Sigmund Freud in collaboration with Josef Breuer, the case of Anna O. The return to a classic clinical case has allowed us to rework the relationship between consciousness and the psychic in the light of developments made by phenomenology and existential psychoanalysis. Freud’s discoveries, in collaboration with Josef Breuer in the historical context of the 19th century, enabled important advances to be made with regard to psychic dynamism as a qualitatively distinct phenomenon from neurological determinations. Freud thus paved the way for research and clinical intervention in a utterly new sense, linked from then on to the historicity of the subject. Re-analyzing the findings of Anna O.’s clinical case in the light of phenomenology and existential psychoanalysis has allowed us to grasp the dialectical tensions between consciousness and the psychic, which we believe were underdeveloped by Freudianism, and in this way, to recover the important theoretical status of consciousness in the constitution and transformation of the psychic, as well as to postulate a new way of defining the psyche based on the notion of exis psychic. Our aim is, therefore, to develop a dialectical understanding between consciousness and the psychic that recovers the essential role of the contingency of consciousness in the constitution of the psychic, as well as to apprehend in a new way the conditioning role of the psyche and its symptoms in the face of lived experiences.